The Influence of Religiosity and Emotional Maturity on the Tendency of Husband's Verbal Violence to Wife - Sillakhudin Sillakhudin (Insan Akademika Publications, 2025)
Domestic violence remains a persistent and multifaceted issue in Indonesian society, affecting families across educational and economic backgrounds. While physical violence is more visible, verbal abuse within marriages often goes unnoticed and unaddressed due to prevailing patriarchal norms and cultural justifications. This study aims to examine the correlation between husbands’ levels of religiosity and emotional maturity and their tendencies toward committing domestic violence, particularly verbal abuse against wives. Using a correlational quantitative design, data were collected from 70 married male employees and students at Universitas 17 Agustus 1945 Samarinda, selected through purposive random sampling. Three psychometric scales were employed to measure religiosity, emotional maturity, and domestic violence tendencies. Statistical analysis using multiple linear regression revealed a significant negative correlation between religiosity and domestic violence (r = -0.265, p < 0.05), as well as between emotional maturity and domestic violence (r = -0.336, p < 0.01). Furthermore, both independent variables jointly contributed significantly to the dependent variable (R = 0.429; F = 7.552; p < 0.01), with emotional maturity accounting for a larger portion of the variance. These findings suggest that higher levels of religiosity and emotional maturity are associated with a reduced likelihood of husbands engaging in domestic violence. This study underscores the importance of fostering spiritual development and emotional regulation as preventative strategies against spousal abuse. Practical implications include the need for integrated educational and counseling interventions that focus on moral values and emotional competence to strengthen family resilience